1993
DOI: 10.1137/0153016
|View full text |Cite
|
Sign up to set email alerts
|

Mode Localization in a Class of Multidegree-of-Freedom Nonlinear Systems with Cyclic Symmetry

Abstract: The free oscillations of n-degree-of-freedom (DOF) nonlinear systems with cyclic symmetry and weak coupling between substructures are examined. An asymptotic methodology is used to detect localized nonsimilar normal modes, i.e., free periodic motions spatially confined to only a limited number of substructures of the cyclic system. It is shown that nonlinear mode localization occurs in the perfectly symmetric, weakly coupled structure, in contrast to linear mode localization, which exists only in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…The prediction is corrected by a shooting procedure in order to solve (7) in which the variations of the initial conditions and the period are forced to be orthogonal to the predictor step. At iteration k, the corrections…”
Section: Corrector Stepmentioning
confidence: 99%
See 3 more Smart Citations
“…The prediction is corrected by a shooting procedure in order to solve (7) in which the variations of the initial conditions and the period are forced to be orthogonal to the predictor step. At iteration k, the corrections…”
Section: Corrector Stepmentioning
confidence: 99%
“…Wei and Pierre examined the effects of dry friction on a nearly cyclic structure using the harmonic balance method [5]. In a series of papers, Vakakis and co-workers demonstrated that, in contrast to the findings of linear theory, nonlinear mode localization may occur in perfectly cyclic nonlinear systems [6,7,8,9]. Other studies dealing with mode localization in nonlinear cyclic systems are [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Localization in both linear and non linear dynamical systems has been studied by many researchers. Samples can be found in [3][4][5][6][7][8]. In a previous study of localization in systems of multiple vibration absorbers, Alsuwaiyan and Shaw [9] investigated the existence of localization in free vibration modes for both translational and torsional vibration absorber systems.…”
Section: Introductionmentioning
confidence: 99%